A General Equilibrium Model with Real Exchange Rates - Leonardo Tariffi (Economies)
In this paper, the Balassa–Samuelson–Tariffi effect is revisited. This research first aims to explain that the behaviour of the real exchange rate shows structural breaks in the short term. A partial equilibrium model “á la Rogoff” is formally formulated where there are relative prices of non-tradable goods in terms of tradable goods in the supply side. Secondly, a general equilibrium model is built after a utility function is added to the partial equilibrium model. It is presented as a mathematical mechanism that shows a stationary state in the real exchange rate considering not only non-tradable goods but also tradable goods both in the domestic market and the foreign market. It is explained that any change in a currency’s price in terms of another currency in real terms is transitory in the long run, thereby disappearing after a certain period of time. In the general equilibrium model, any price’s change in non-tradable goods will be compensated by either a price’s change in tradable goods or changes in the nominal exchange rate. Therefore, this study’s main contribution is to show theoretically that the real exchange rate is constant over time in the long run.